Avaliação da adição de Nanosílica e silicato de sódio em pastas de cimento para poços de petróleo com baixo gradiente de fratura - Queiroz Júnior, Manoel Ivany de (2013)
The oil wells cementing is a critical step during the phase of well drilling, because problems during the operation of slurry pumping and an incomplete filling of the annular space between the metal casing and the formation can cause the slurry loss. Therefore, the slurry adopted in primary cementing an oil well must be properly dosed so that these problems are avoided during its pumping. When you drill a well in a weak rock formation requires even more careful, because should be a limit of hydrostatic pressure exerted during cementation, that does not occur rock collapse. With the objective of performing the cementing of a well whose formation is weak or unconsolidated are employed lighter slurries. Thus, this study used slurries with sodium silicate and nano silica in concentrations of 0,1; 0,4; 0,7 e 1,0 gpc, in which the slurries with nano silica showed the rheological parameters higher concentrations of up to 0.7 gpc and for concentration of 1.0 the slurry with sodium silicate obtained the highest values, remaining above the limits for application in fields, mainly wells with low fracture gradient, because a significant increase in viscosity may result in an increase in pressure pumping in operations of secondary cementations. Furthermore, there was no decrease in strength with increasing concentration of additive. Then, it is possible use of these additives to formulate Lighter slurry